Muslim Students In Catholic Religious Education In Indonesia: Interfaith Learning and Socio-Religious Identity Negotiation - Mahin Anas Ramadona; Irfan Musonif; Semi Priyatno (IJGIE (International Journal of Graduate of Islamic Education), 2026)
This study addresses the limited empirical understanding of how Muslim students negotiate their socio-religious identity within Catholic Religious Education (CRE) in Indonesian faith-based schools. While interfaith learning has been widely promoted, little is known about how minority students interpret and engage with religious differences in classroom contexts. This study aims to examine the processes through which Muslim students construct meaning and maintain their religious identity in interfaith learning settings. Using an interpretive phenomenological approach, this research involved nine participants, including Muslim students, students from other religious backgrounds, a religion teacher, and a school principal. Data were collected through semi-structured interviews and classroom observations conducted between January and February 2026, and analyzed using thematic analysis. The findings indicate that students undergo a process of socio-religious identity negotiation, characterized by initial uncertainty, adaptive participation, and selective engagement with religious content. Dialogical and non-coercive pedagogy enables students to reinterpret religious differences through shared moral values without compromising their beliefs. This study highlights the role of inclusive religious education in fostering reflective religiosity and interfaith understanding in pluralistic contexts.